The strategy of developping group guidance model based on experience as a preventive effort LGBT behavior in student - Neviyarni Neviyarni (Fakultas Ilmu Pendidikan UNP)
This article aims to present the strategy of developing an experience-based group guidance model as an effort to prevent LGBT behavior on students. Specifically, it aims to discuss: (1) practical needs and strategic needs that include student needs, counselor needs, achievement needs, institutional needs and situational needs; (2) the profile of student needs for experience-based group guidance as an effort to prevent LGBT behavior on students 3) based on the needs analysis, a need map is made to determine the service materials to be provided (4) the development of the guidance model of the group as an effort to prevent LGBT behavior on the students and (5) model validation through the implementation of experience-based group counseling model as an effort to prevent LGBT behavior on college student. With this strategy is expected to be developed model of experience-based group guidance as an effort to prevent LGBT behavior on students.